Automated inventory management system on Android using barcodes and QR-codes - Haidukevych, Y.O.; Doroshenko, А.Yu. (Інститут програмних систем НАН України, 2022)
A software is developed for inventory automation based on Android using the Firebase database in the Java programming language. The appendix uses a system of reading barcodes and QR-codes, which provide the addition of goods to the warehouse with all the details of the selected product and informationon all stocks in the warehouse with their price, category, name and code goods. Implemented authorization of system users using the open FirebaseAuth standard. Creating a single service for authorization and registration allows to make the system scalable. The system implements the search for goods by code, as well as viewing stocks in the warehouse with automatic price calculation. The main service of the database is a cloud database of the NoSQL class, which allows storing and synchronizing data between several clients, there is an API for data encryption. In addition, the database remains available only in the application to avoid unauthorized access and editing. While development, it was decided to make an automated control system on the Android OS device, because industrial digitalization (precisely because of the mass introduction of smart devices) requires mobility and accelerated processing of stocks at various stages of turnover. Testing of the developed software is carried out.Problems in programming 2022; 1: 13-22